Pengaruh Islamic Branding, Viral Marketing, Harga dan Lokasi terhadap Keputusan Pembelian - Erna Herawati; Agung Guritno (Politeknik Baubau, 2023)
This study aims to determine the effect Islamic Branding, Viral Marketing, Price and Location of Purchasing Decisions. The observation model used in this research is quantitative research by processing primary data obtained through distributing questionnaires to consumers of Geprek Assalam 99. The samples taken in this research are all buyers of Ayam Geprek Assalam 99 who have purchased the product at least once. The sample in this research is 100 respondents using the technique purposive sampling, then the results obtained were processed using SPSS version 26. The analysis used included descriptive statistical tests, instrument tests, classical assumption tests, multiple linear regression tests, model accuracy tests and hypothesis testing. The results obtained in this study are Islamic branding has a positive but not significant effect on purchasing decision, viral marketing gives a positive and significant influence on purchasing decisions, prices are positive and significant on purchasing decisions and location positive but not significant impact on purchasing decisions.